A Comparative Transcriptional Landscape of Two Castor Cultivars Obtained by Single-Molecule Sequencing Comparative Analysis - Zhou, Yaxing; Zhu, Guoli; Wang, Yun; He, Zhibiao; Zhou, Wei (Frontiers in Genetics, 2021)
Background and Objectives: Castor (Ricinus communis L.) is an important non-edible oilseed crop. Lm-type female strains and normal amphiprotic strains are important castor cultivars, and are mainly different in their inflorescence structures and leaf shapes. To better understand the mechanisms underlying these differences at the molecular level, we performed a comparative transcriptional analysis. Materials and Methods: Full-length transcriptome sequencing and short-read RNA sequencing were employed. Results: A total of 76,068 and 44,223 non-redundant transcripts were obtained from high-quality transcripts of Lm-type female strains and normal amphiprotic strains, respectively. In Lm-type female strains and normal amphiprotic strains, 51,613 and 20,152 alternative splicing events were found, respectively. There were 13,239 transcription factors identified from the full-length transcriptomes. Comparative analysis showed a great variety of gene expression of common and unique transcription factors between the two cultivars. Meanwhile, a functional analysis of the isoforms was conducted. The full-length sequences were used as a reference genome, and a short-read RNA sequencing analysis was performed to conduct differential gene analysis. Furthermore, the function of DEGs were performed to annotation analysis. Conclusion: The results revealed considerable differences and expression diversity between the two cultivars, well beyond what was reported in previous studies and likely reflecting the differences in architecture between these two cultivars.